2016
DOI: 10.2214/ajr.15.15542
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic Carcinoma of the Lung: Relationship Between CT Findings and Prognosis

Abstract: A massive central low-attenuation area or cavity on CT was the only predictor of overall survival and disease-free survival in patients with lung PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
3
13
1
Order By: Relevance
“…Fujisaki et al . reported that a massive central low‐attenuation area or cavity on CT, which both represent tumor necrosis, were predictors of poor survival in patients with PC of the lung 7. Conversely, in this study, the presence of a low‐attenuation area was not found to be prognostic; by contrast, air bronchogram was found to be a favorable prognostic factor.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Fujisaki et al . reported that a massive central low‐attenuation area or cavity on CT, which both represent tumor necrosis, were predictors of poor survival in patients with PC of the lung 7. Conversely, in this study, the presence of a low‐attenuation area was not found to be prognostic; by contrast, air bronchogram was found to be a favorable prognostic factor.…”
Section: Discussioncontrasting
confidence: 72%
“…Pleomorphic carcinoma of the lung has a poor prognosis compared with other types of non‐small cell lung cancer . Previous studies examined the prognostic impacts of the clinicopathologic characteristics of PC of the lung, and showed that massive coagulative necrosis or a massive central low‐attenuation area of the tumor were negative prognostic factors . Coagulative necrosis observed in PC of the lung would suggest rapid proliferation of the tumor; in addition, it may facilitate systemic tumor dissemination through impairment of tumor vasculature .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, we can determine that a tumor is GCLC by using CT, which shows a large and central low-attenuation area or cavity. This imaging is consistent with the tumor necrosis area found in pathological specimens [5]. There are data showing that the palliative chemotherapy response in advanced lung sarcomatoid carcinoma is poor [6].…”
Section: Introductionsupporting
confidence: 84%
“…The benefits of surgery are less clear in patients with nodal metastasis. Raveglia et al (19) and Yuki et al (20) reported statistically significant differences in the OS of patients with pN0 and pN+ tumors, but Fujisaki et al found that the presence of lymph node metastasis at surgery did not predict OS or disease-free survival in another series of 44 patients (22). A 9-month benefit in median OS was seen in pN0 patients compared with pN1 patients who underwent surgery, but the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 96%